Mean Level Differences in the Vividness, Meaning, and Coherence of Life Story High and Low Points: How Valenced Life Stories Do and Do Not Differ. Issue 2 (3rd April 2019) - Cox, Keith S.; McAdams, Dan P.
ABSTRACT: The current paper examines systematic differences in life story high and low points. Narratives from a young adult sample (n = 145) and a late midlife adult sample (n = 154) were coded for vividness, meaning, and coherence. An automated linguistic coding technique was also used. Mean level comparisons found high and low points had similar levels of vividness and coherence. Among the young adults, but not the late midlife adults, there was greater total meaning making (positive and negative combined) in low points than in high points. Across high and low points, levels of positive meaning were greater than negative meaning, in both samples, suggesting a positivity bias in meaning making in valenced life stories. Moreover, the bias was large in both samples (68% in young adults, 450% in late midlife adults). Preliminary analyses suggested midlife adults, when compared to young adults, had a greater bias towards producing more positive than negative meaning. In both samples, automated linguistic analyses indicated that low points displayed greater word counts and usage of cognitive mechanism words, suggesting greater cognitive processing in low points at the level of word usage. Findings are framed within autobiographical memory and narrative research and socioemotional selectivity theory.